Make‐or‐buy decisions for industrial additive manufacturing. Issue 4 (21st March 2022) - Friedrich, Anne; Lange, Anne; Elbert, Ralf
Abstract: Much of the potential of industrial additive manufacturing (AM) is said to lie in the digital specification of components that can be transmitted seamlessly and unambiguously to partners fostering flexible outsourcing. In industry, we observe nuanced AM supply chain governance structures that result from make‐or‐buy decisions, with a tendency to implement AM in‐house. Thus, there is a discrepancy between what is discussed in the literature and implemented in practice. We apply a multiple‐case study approach to investigate why and how AM impacts the make‐or‐buy decision of manufacturing firms. We identify four decision profiles demonstrating the spectrum of specific governance structures and develop a framework to explain the underlying rationales. We find strong arguments for in‐house AM including firms' perceived need to protect their digitally encapsulated intellectual property, reevaluation of their core competencies, commitment to internal learning, and senior management's enthusiasm for AM. By using transaction cost economics and the resource‐based view, we contribute to the understanding of how arguments of these general theories are modified by the digital and emerging traits of AM. We reveal contradicting guidance in the theories' argumentation for the case of AM and provide managers a clear perspective on alternative strategies for their AM implementation process.